The Development of Agos Motor Workshop Booking and Inventory Management System - Mohammad, Nur Izzah Hannani; Nur Ariffin Mohd Zin (Applied Information Technology And Computer Science, 2025)
Agos Motor Workshop Booking and Inventory Management System is a web-based system that allows the organization to manage interrelated parts of its’ business. The system has been developed to solve all the problems by using Prototyping Model methodology and three-tier client-server system architecture. Agos Motor Workshop Booking and Management System should allow the owner to manage the appointment booking, inventory, sales, and service task of the workshop on the line. The system should also allow the customer to make orders of the spare parts and booking appointment services through online. This system is expected to manage the inventory of spare parts and services information for the Bengkel Agos Motor in a more systematic way. These contributions are promoting a better working environment for Bengkel Agos Motor in the future.